2019
DOI: 10.1002/joc.6002
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of various types of El Niño–Southern Oscillation (ENSO) and ENSO Modoki on the rainy season over the Huaihe River basin

Abstract: Precipitation is a significant parameter in many aspects such as agriculture, water management and climate variability. To characterize rainy season variations is important to understand precipitation variability under the effect of climate change. In this study, rainy season features (i.e., onset, retreat and rainy‐season precipitation) over the Huaihe River basin (HRB) and the response to different types of El Niño–Southern Oscillation (ENSO), that is, central Pacific warming (CPW), eastern Pacific warming (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…The ENSO Modoki was first reported by Ashok et al (2007), who highlighted that it influenced the regional climate of East Asia in a different way from the typical ENSO. Since then, many other studies have shown that the canonical ENSO and the ENSO Modoki have opposite effects on precipitation in the Yangtze River basin and South China (Cao et al, 2019;Chen et al, 2017;Feng & Li, 2011;Karori et al, 2013;Yuan & Yang, 2012;Zhang et al, 1996). The Indian Ocean Basin mode (Hu & Duan, 2015) and the Indian Ocean Dipole mode (Qiu et al, 2014;Weng et al, 2011) also contribute to the distribution of precipitation in China, whereas the North Atlantic Oscillation affects summer precipitation in the Yangtze River basin and South and Southwest China (Gu, Li, Wang, et al, 2009;Linderholm et al, 2011;Sung et al, 2006;Xu et al, 2001;Zhou, 2013) and the timing of the onset of the Meiyu rainy season (Xu et al, 2001).…”
Section: Relationship Between the Onset Of The Rainy Season And The Lmentioning
confidence: 99%
“…The ENSO Modoki was first reported by Ashok et al (2007), who highlighted that it influenced the regional climate of East Asia in a different way from the typical ENSO. Since then, many other studies have shown that the canonical ENSO and the ENSO Modoki have opposite effects on precipitation in the Yangtze River basin and South China (Cao et al, 2019;Chen et al, 2017;Feng & Li, 2011;Karori et al, 2013;Yuan & Yang, 2012;Zhang et al, 1996). The Indian Ocean Basin mode (Hu & Duan, 2015) and the Indian Ocean Dipole mode (Qiu et al, 2014;Weng et al, 2011) also contribute to the distribution of precipitation in China, whereas the North Atlantic Oscillation affects summer precipitation in the Yangtze River basin and South and Southwest China (Gu, Li, Wang, et al, 2009;Linderholm et al, 2011;Sung et al, 2006;Xu et al, 2001;Zhou, 2013) and the timing of the onset of the Meiyu rainy season (Xu et al, 2001).…”
Section: Relationship Between the Onset Of The Rainy Season And The Lmentioning
confidence: 99%
“…Active water vapor could bring enough precipitation to the HRB. Cao et al [45] analyzed the influence of monsoon on rainy-season precipitation in the HRB. Stronger monsoons from the Indian Ocean are related to more rainfall in the HRB.…”
Section: Meteorological Patterns Associated With the Hidden Statesmentioning
confidence: 99%
“…El Niño, as the warm phase of ENSO, generally develops in boreal summer and the early autumn, reaches its peak in boreal winter, and decays in the following spring and summer (An and Wang 2001;Tozuka and Yamagata 2003;Lau et al 2005;Xie et al 2009). It has different climate effects on the EASM during different phases (Huang and Wu 1989;Wu et al 2003Wu et al , 2009Cao et al 2019;Yong and Huang 2019). For the El Niño decaying summer, an anomalous anticyclone exists over the Northwest Pacific (NWP).…”
Section: Introductionmentioning
confidence: 99%